Elevating NagZ Improves Resistance to β-Lactam Antibiotics via Promoting AmpC β-Lactamase in Enterobacter cloacae - Yang, Xianggui; Zeng, Jun; Zhou, Qin; Yu, Xuejing; Zhong, Yuanxiu; Wang, Fuying; Du, Hongfei; Nie, Fang; Pang, Xueli; Wang, Dan; Fan, Yingzi; Bai, Tingting; et al. (Frontiers in Microbiology, 2020)
Enterobacter cloacae complex (ECC), one of the most common opportunistic pathogens causing multiple infections in human, is resistant to β-lactam antibiotics mainly due to its highly-expressed chromosomal AmpC β-lactamase. It seems that regulation of chromosomal AmpC β-lactamase is associated with peptidoglycan recycling. However, underlying mechanisms are still poorly understood. In this study, we confirmed that NagZ, a glycoside hydrolase participating in peptidoglycan recycling in Gram-negative bacteria, plays a crucial role in developing resistance of Enterobacter cloacae (EC) to β-lactam antibiotics by promoting expression of chromosomal AmpC β-lactamase. Our data shows that NagZ was significantly up-regulated in resistant EC (resistant to at least one type of the third or fourth generation cephalosporins) compared to susceptible EC (susceptible to all types of the third and fourth generation cephalosporins). Similarly, the expression and β-lactamase activity of ampC were markedly enhanced in resistant EC. Moreover, ectopic expression of nagZ enhanced ampC expression and resistance to β-lactam antibitics in susceptible EC. To further understand functions of NagZ in β-lactam resistance, nagZ-knockout EC model (ΔnagZ EC) was constructed by homologous recombination. Conversely, ampC mRNA and protein levels were down-regulated, and resistance to β-lactam antibiotics was attenuated in ΔnagZ EC, while specific complementation of nagZ was able to rescue ampC expression and resistance in ΔnagZ EC. More interestingly, NagZ and its hydrolysates 1,6-anhydromuropeptides (anhMurNAc) could induce the expression of other target genes of AmpR (a global transcriptional factor), which suggested that the promotion of AmpC by NagZ is mediated AmpR activated by anhMurNAc in EC. In conclusion, these findings provide new elements for a better understanding of resistance in EC, which is crucial for the identification of novel potential drug targets.